How much is invested in obesity prevention in Australia? An analysis of major research and Federal Government funding, 2013-2022 - Huong Ngoc Quynh Tran; Moosa Al Subhi; Nicole Ward; Phuong Nguyen; Marufa Sultana; Jaithri Ananthapavan; Vicki Brown (Sax Institute, 2024)
Objective and importance of study: Overweight and obesity are the second leading risk factors for death and non-communicable disease in Australia. This study aimed to examine the Australian Federal Government funding landscape for population-level obesity prevention from 2013 to 2022. Study type: A retrospective analysis and narrative synthesis of publicly available data on obesity prevention funding from the Federal Government and major federally funded Australian research organisations. Methods: Searches were conducted of Australian Federal Government Budget documents and funding announcements from the National Health and Medical Research Council (NHMRC), Australian Research Council (ARC) and Medical Research Future Fund (MRFF). Funding allocations targeting obesity prevention, or the prevention of risk factors associated with obesity, were included. These were determined by the presence of keywords related to obesity, unhealthy diet, physical activity and sedentary behaviour. Data were extracted verbatim, coded and narratively synthesised by funding source. Results: From 2013 to 2022, 186 funding allocations for obesity prevention in Australia were identified, totalling approximately A$778 million. The proportion of funding allocated to obesity prevention compared to the total annual budget of each funding source was relatively low: NHMRC = 1.1%; ARC = 0.2%; MRFF = 0.8%; Federal Government = 0.1% (of health budget). Funding for obesity prevention initiatives fluctuated over time. Conclusions: Findings underscore the need for strategic and ongoing funding allocation to support obesity prevention research, implementation and sustainment of evidence-based obesity prevention initiatives in Australia.